L'éducation aux controverses en prison - Valérie Radawiec (Université de Provence, 2022)
This research aims at leading philosophical discussions on moral dilemmas with adult inmates. The moral dilemma deals with a fictitious or real situation whose outcome raises a moral issue with restricted choices between two contradictory possibilities. Actually, the moral dilemma generates a big controversy among the participants in the course of the philosophical discussions. Our research's goal is to teach the prisoners how to take part in a controversial debate in order to participate in their moral development. Methodologically, we use a qualitative method, the analysis of the content. From the analysis of the verbatim transcripts of the discussions on the moral dilemmas, we highlight the values ​​which guide the moral judgments of the detained persons, taking into account the rational and emotional dimensions aroused in the subjects. Then, we try to understand the level of the prisoners' moral development by referring to Kohlberg's phases of moral development theory. This reflective work on the dilemma aims at the moral educability of the subject, based on the postulate that inmates' educability is still possible.